Six versus twelve weeks of Swedish massage therapy for generalized anxiety disorder: Preliminary findings. (January 2021) - Rapaport, Mark Hyman; Schettler, Pamela J.; Larson, Erika R.; Dunlop, Boadie W.; Rakofsky, Jeffrey J.; Kinkead, Becky
Abstract: Acute treatment of Generalized Anxiety Disorder often requires 3 months or more of care in order to optimize response. As part of an exploratory grant we have previously demonstrated that six weeks of twice-weekly Swedish Massage Therapy (SMT) was more effective than an active control in decreasing Hamilton Anxiety Rating Scale Scores (HAM-A). An additional goal of this project was to determine if an additional six weeks of twice-weekly SMT led to greater clinical and statistical benefit. We found that HAM-A scores did continue to decrease with an additional six weeks of therapy but that the greatest benefit occurred during the first versus the second 12 sessions (−9.91 vs.−3.09, t = 2.21; df = 10; p = 0.052). These preliminary findings suggest that the majority of benefit in symptom reduction occurs in the first six weeks and that six weeks of twice-weekly SMT may be sufficient for the majority of patients.